2021
DOI: 10.3389/fpls.2021.677767
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology and Rhizosphere Characteristics Are Related to Salt Tolerance of Suaeda salsa and Beta vulgaris L.

Abstract: Halophytes are capable of resisting salinity, and their root system is the part in direct contact with the saline soil environment. The aim of this study was to compare the responses of root morphology and rhizosphere characteristics to salinity between a halophyte, Suaeda salsa (suaeda), and a glycophyte, Beta vulgaris L. (sugar beet). The soil salt content was set to four levels (0.7, 1.2, 1.7, and 2.7%) by NaCl-treated plants. We investigated the soil pH, EC, nutrients and soil, plant ion (Na+, Cl−, K+, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…Additionally, an appropriate N level benefits halophytes, allowing them to increase their salt-tolerance capabilities. In addition, this study showed that a greater root length occurred at the 1.0% salt level, which was similar to the results of Wang et al [ 25 ]. This suggested that a certain amount of salt promotes the root formation of halophytic plants, whereas levels exceeding the threshold inhibit root formation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, an appropriate N level benefits halophytes, allowing them to increase their salt-tolerance capabilities. In addition, this study showed that a greater root length occurred at the 1.0% salt level, which was similar to the results of Wang et al [ 25 ]. This suggested that a certain amount of salt promotes the root formation of halophytic plants, whereas levels exceeding the threshold inhibit root formation.…”
Section: Discussionsupporting
confidence: 91%
“…To adapt to the non-homogeneity of nutrients and salt, root growth might show a strong plasticity response [ 24 ]. Moderate salt levels displayed a positive effect on root development for halophyte, but the stress from higher salt levels causes a negative effect, where it obtains more nutrients by increasing fine root presence in the subsoil [ 25 ]. N application would be bound to alter nutrient distributions in the topsoil and subsoil, which might produce an important influence on root architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the different results on root morphology of beet cultivars [61,81], alterations in root length are important adaptive strategies for plant stress tolerance [11,25,153]. Sugar beet and fodder beet are deep-rooted crops [40,48,63], and under water deprivation, fodder beet is able to extract water from bottom soil layers [63].…”
Section: Selection Of Salt-and Drought-tolerant Beets Based On Different Parametersmentioning
confidence: 99%
“…Sugar beet and fodder beet are deep-rooted crops [ 40 , 48 , 63 ], and under water deprivation, fodder beet is able to extract water from bottom soil layers [ 63 ]. However, sugar beet plants exposed to salt or drought stress displayed lower root length as compared to unstressed plants [ 54 , 153 ]. Among different sugar beet genotypes, salt-tolerant one (H30917) displayed longest root length as compared to other genotypes under salt stress [ 25 ].…”
Section: Morpho-physiological Biochemical and Molecular Changes Under Salinity And Droughtmentioning
confidence: 99%
See 1 more Smart Citation